Implementation of the Independent Curriculum in Islamic Education Subjects at SMPN 70 Jakarta - Khoirunnisa Istiqomah; Lismawati, Lismawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim of this research is to determine the implementation of the Merdeka Belajar curriculum in Islamic Religious Education (PAI) and Characteristics subjects at SMPN 70 Jakarta. This research uses a qualitative descriptive approach, namely by direct observation and collecting actual information from various scientific journals. The research results at SMPN 70 Jakarta are still not optimal. The implementation of the independent curriculum provides good changes to the learning process at SMPN 70 Jakarta so that children's learning patterns are more interactive, have a critical and creative mindset, and are independent of learning activities in class. Meanwhile, the obstacles identified include challenges in creating a fun and quality learning atmosphere, as well as difficulties in determining content and themes that suit students' interests and talents.